2015
DOI: 10.4236/ojst.2015.52005
|View full text |Cite
|
Sign up to set email alerts
|

The Color of Natural Teeth Investigated by Visual Perception and Spectrophotometer

Abstract: The advantage of electronic devices is to eliminate the subjectivity. Based on individual capabilities, visual perception has its disadvantages. The aim of this study was to find out the possible shade difference between the upper and lower teeth, visual perception versus spectrophotometry as well as proving that females are better in visual perception of colour matching. 82 subjects (dental students) of this study determined the color of each other's natural teeth. The color of 1640 teeth (incisors, canines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As proven by several studies, [21][22][23][24][25][26][27][28] the spectrophotometer used in the present study was found to be consistent and more objective than the visual shade guides and helped eliminate the effect of different light sources and inter examiner bias.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As proven by several studies, [21][22][23][24][25][26][27][28] the spectrophotometer used in the present study was found to be consistent and more objective than the visual shade guides and helped eliminate the effect of different light sources and inter examiner bias.…”
Section: Discussionmentioning
confidence: 55%
“…14,16,19 Several color space systems are available to describe color, with the Munsell and CIE systems being the most widely used, the Munsell system describes color in three dimension using three coordinates, the hue, value, and chroma, on the other hand, the CIE system uses three coordinates, L* a* b*, to describe color where L* is the lightness axis from black to white, a* is the red-green axis, b* is the yellow-blue axis, and ΔE is the color difference value that represents the color perception; only ΔE values between 1 and 2 are considered clinically acceptable, whereas values above or less than these would implicate a high degree of intra-and interexaminer variability, and render the use of digital shade matching devices more useful to minimize the subjectivity of color assessment. [20][21][22][23][24][25][26][27][28][29] Gingival color was found to be related to gender, age, and skin color of different ethnic origins, however, very little data exists regarding the color relation between the gingiva and the teeth. [30][31][32][33] Different gingival colors and pigmentations, and inadequacy of available gingival visual shade guides further complicate the situation and hinder the clinician from further investigations into pink esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Through optical phenomena, light is absorbed, reflected, and transmitted by the tooth surface. 9 Color perception is influenced by three variables: the light source, the object, and the observer's eyes and brain. 10 Object color is the result of a perception of light reflected or scattered from its surface.…”
Section: Introductionmentioning
confidence: 99%